A Systematic Review of Wearable Devices for Orientation and Mobility of Adults with Visual Impairment and Blindness - Santos, Aline Darc Piculo Dos [UNESP] (2021)
Wearable devices have been developed to improve the navigation of blind and visually impaired people. With technological advancements, the application of wearable devices has been increasing. This systematic review aimed to explore existing literature on technologies used in wearable devices to provide independent and safe mobility for visually impaired people. Searches were conducted in six electronic databases (PubMed, Web of Science, Scopus, Cochrane, ACM Digital Library and SciELO). Our systematic review included 61 studies. The results show that the majority of studies used audio information as a feedback interface and a combination of technologies for obstacle detection-especially the integration of sensor-based and computer vision-based technologies. The findings also showed the importance of including visually impaired individuals during prototype evaluation and the need for including safety evaluation which is currently lacking. These results have important implications for developing wearable devices for the safe mobility of visually impaired people.